2018
DOI: 10.1177/2151459318769508
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Comorbidities and Age on Functional Outcomes After Total Knee Arthroplasty in the Octogenarian: A Matched Cohort Study

Abstract: Introduction:According to the World Health Organization data repository, the average life expectancy at birth for Singapore in 2015 has risen to 83.4 years, and many octogenarians (OG) remain active socioeconomically. The aim of this study is to compare the improvement and the impact of comorbidities on functional recovery after total knee arthroplasty (TKA) between OG and their younger counterparts.Methods:This is a retrospective study of prospectively collected data from a single institution arthroplasty reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…Результаты нашей работы не подтвердили зависимость функциональных исходов от возраста. Некоторые исследователи объясняют повышенную инвалидизацию у пожилых пациентов после госпитального лечения высокой частотой сопутствующей патологии, осложняющей течение основного заболевания и препятствующей проведению реабилитации [23]. Вероятно, возраст сам по себе не влияет на скорость функционального восстановления и прогнозирует результат в меньшей степени, чем другие клинические показатели [24].…”
Section: Discussionunclassified
“…Результаты нашей работы не подтвердили зависимость функциональных исходов от возраста. Некоторые исследователи объясняют повышенную инвалидизацию у пожилых пациентов после госпитального лечения высокой частотой сопутствующей патологии, осложняющей течение основного заболевания и препятствующей проведению реабилитации [23]. Вероятно, возраст сам по себе не влияет на скорость функционального восстановления и прогнозирует результат в меньшей степени, чем другие клинические показатели [24].…”
Section: Discussionunclassified
“…While the average number of inpatient days decreased from 9.4 to 4.2 days, the percentage of discharged patients transferring to rehabilitation wards increased from 10% to 38% (Vincent, Vincent, Lee, & Alfano, ). According to the literature, previous studies found that patients’ joint and body functions are able to sufficiently recover by 3–6 months after TKA, resulting in high patient satisfaction levels (Cher et al, ; Kennedy, Stratford, Hanna, Wessel, & Gollish, ; Lin, Chang, & Chuang, ; Maruyama et al, ; Naal et al, ). Cher et al () followed 209 TKA patients for 2 years and found that patients reached the largest improvement during the first 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, previous studies found that patients’ joint and body functions are able to sufficiently recover by 3–6 months after TKA, resulting in high patient satisfaction levels (Cher et al, ; Kennedy, Stratford, Hanna, Wessel, & Gollish, ; Lin, Chang, & Chuang, ; Maruyama et al, ; Naal et al, ). Cher et al () followed 209 TKA patients for 2 years and found that patients reached the largest improvement during the first 6 months. Naal et al followed 233 TKA patients before surgery, and at 3, 6 and 12 months after surgery, and found that as assessed by patient‐reported outcomes over time, at 12 months more than 90% of the patients were satisfied with the surgical results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cher et al studied the functional scoring between octogenarians and younger patients in TKA at 6 and 24 months[29]. Both groups showed statistical improvement in KSS and KFS post-operatively.…”
mentioning
confidence: 99%